The Influence of Characteristics Individual’s Investor on Financial Investment Decision of Young Generation - Sari, Ayula Candra Dewi Mulia; Husodo, Zaäfri Ananto (Jurnal Samudra Ekonomi dan Bisnis, 2025)
This study aims to determine influence of individual investor characteristics, including financial literacy, overconfidence bias, herding behavior, risk tolerance and demographic factors on the financial asset investment decisions of young generation. This study used purposive sampling, with sample consisting of capital market investors within age range of gen Y and gen Z and location of domiciles in five major cities on Java. Primary data were collected through an online questionnaire, with a total of 195 investors. Hypotesis testing was conducted using binary logistic regression model and processed with STATA-17. Result of the study indicate that overconfidence bias, herding behavior, risk tolerance and gender influence financial investment decisions of young generation. But financial literacy, income and age do not have a significat effect on investment decision of young generation.